Exploring the Potential of Glutathione Reductase Overexpression to Improve Tellurium Nanoparticle Production in Escherichia Coli - Arenas-Salinas, F; Mura-Mardones, F (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Tellurium nanoparticles (TeNPs) are emerging as valuable materials in various technological and biomedical applications due to their unique physicochemical properties. In general, TeNPs are prepared using chemical methods based on a redox reaction in which strong reducing agents are employed which are often toxic and harmful to the environment. Biological biosynthesis provides a green strategy for substituting the commonly used reducing chemical agents with microorganisms or enzymes. Among the enzymes noted as key players in microbial tellurite reduction, glutathione reductase (GR) has been identified; however, its specific role in enhancing TeNP biosynthesis has yet to be fully elucidated. In this study, we aimed to evaluate the impact of GR overexpression on TeNP production in Escherichia coli (E. coli). For this purpose, four GR enzymes from different microorganisms identified as tellurite resistant were heterogeneously expressed and purified from E. coli. The kinetic parameters for NADPH and oxidized glutathione (GSSG), the native substrates of GR, were determined to evaluate their TR activity under saturated NADPH concentrations. The GR from Pseudomonas lini strain BNF22 presented the highest catalytic efficiency for NADPH and exhibited greater TR activity. This enzyme was overexpressed in E. coli MG1655 (DE3) and cells overexpressing GR increased the yield of TeNPs in those cells, presenting an increased elemental cell tellurium composition. Our results provide valuable insights for the development of engineered E. coli as a platform for TeNP biosynthesis. Using microorganisms as a green strategy for TeNP production, the results of this study highlight the enzymatic mechanisms underlying the role of GR in the biosynthesis of TeNPs. © 2025 by the authors.